Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together Berbantuan Media Ensiklopedia dan LKPD Ular Tangga Untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Andrew Setiawan Ratu Djingi; Yohana Makaborang; Riwa Rambu Hada Enda (Pustaka Digital Indonesia, 2025)
Twenty-first century education demands innovation in learning so that students do not merely receive information passively, but actively construct understanding through interaction, collaboration, and meaningful experiences. This study aims to describe the implementation of the cooperative learning model Numbered Heads Together (NHT), supported by encyclopedia media and a Snakes and Ladders–based Student Worksheet (LKPD), as well as to analyze the improvement of cognitive and affective learning outcomes of Class VIIB students at SMPN SATAP PADAMMU. The urgency of this research lies in the need to identify learning strategies that effectively improve learning outcomes evenly, while also fostering students’ motivation, social engagement, and critical thinking skills. This study employs Classroom Action Research (CAR) with a descriptive quantitative approach. The research subjects consisted of all 21 students in Class VIIB, while data collection instruments included observation sheets and written tests to assess cognitive and affective learning outcomes. The data were analyzed descriptively to observe trends of improvement in each cycle. The results show a significant increase in cognitive aspects, from 28% in the pre-cycle to 61% in Cycle I, and further rising to 85% in Cycle II. Affective learning outcomes also improved, from 66.66% in Cycle I to 100% in Cycle II. These findings indicate that implementing the NHT learning model supported by encyclopedia media and the Snakes and Ladders LKPD is effective not only in enhancing students’ conceptual understanding and cognitive skills, but also in strengthening emotional engagement and social interaction during learning. This research affirms the importance of innovative learning models and media in creating meaningful, contextual, and enjoyable learning experiences for junior high school students. The practical implication is that teachers can adopt cooperative learning strategies supported by interactive media to improve learning outcomes comprehensively and equitably.